Frequency Of Splenomegaly In Patients With Abdominal Ultrasound - Saleem, Sumbal; Zulfiqar, Taiba; Ali, Abid (Medical Science Journal for Advance Research, 2022)
Aims and objectives: To find out the frequency of splenomegaly in patients with abdominal ultrasound Methods: This prospective cross-sectional study was conducted at the Radiology Department of City Care Hospital in Gujranwala. A total of 65 participants with pain in the left upper quadrant were included in the study. Patients ranged in age from 21 to 75 years old, with 37 men and 28 females. Statistical analysis was then performed using SPSS. In individuals with left upper quadrant pain, the frequency of splenomegaly is calculated. Results: Out of 65 patients who presented with splenomegaly, positive cases for splenomegaly reported were 26 and negative cases were 39 Conclusion: For detecting splenomegaly, sonography is a good modality with numerous advantages. It is nonionizing radiation free, relatively inexpensive, widely available, and simple to use, with a high diagnostic effectiveness. Patients who have complained of abdominal pain have been concluded.